2019
DOI: 10.1016/j.bja.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity after sevoflurane anaesthesia: a new twist to an old story

Abstract: EditordAnaesthetic-induced hepatic dysfunction is a complex diagnostic problem. Because of the use of multiple drugs that can cause liver dysfunction, it is often difficult to pinpoint the culprit. Diagnosis of inhalation anaesthetic-related hepatic injury is usually made after other causes have been excluded. Unlike other drugs of this class, sevoflurane has the least hepatotoxic potential as it is not metabolised to reactive intermediates that lead to the formation of hepatotoxic proteins. 1 Using a case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, this is the first prospective study to explore the association between gene polymorphisms and the sedation effect of sevoflurane in patients. Sevoflurane mainly functions as the original drug, and approximately 5% of sevoflurane is biotransformed by CYP2E1 to produce trifluoroacetyl chloride that can lead to drug‐induced liver injury 26 . In this study, CYP2E1 was not incorporated as a candidate gene.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, this is the first prospective study to explore the association between gene polymorphisms and the sedation effect of sevoflurane in patients. Sevoflurane mainly functions as the original drug, and approximately 5% of sevoflurane is biotransformed by CYP2E1 to produce trifluoroacetyl chloride that can lead to drug‐induced liver injury 26 . In this study, CYP2E1 was not incorporated as a candidate gene.…”
Section: Discussionmentioning
confidence: 98%
“…The study did not show, however, significant change in platelet count, PTT, or PT immediately after anesthesia induction [ 8 ]. On the contrary, sevoflurane has previously demonstrated hepatotoxicity and reproducible hepatic dysfunction after anesthesia in patients with no prior history of liver disease [ 9 ]. Sevoflurane is a relatively safe drug in its class; however, its induction of compound A production may play a role in liver insults [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, sevoflurane has previously demonstrated hepatotoxicity and reproducible hepatic dysfunction after anesthesia in patients with no prior history of liver disease [ 9 ]. Sevoflurane is a relatively safe drug in its class; however, its induction of compound A production may play a role in liver insults [ 9 ]. Additionally, repeated exposure to halogenated volatile anesthetics such as sevoflurane may cause drug sensitization further manifesting as hepatotoxicity [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This neurodegenerative disorder is characterised by progressive development of bradykinesia, resting tremor, and rigidity. 1 As the disease progresses, patients develop impaired performance of gross and fine motor skills. 2 A recent study showed that inspiratory muscle strength is also impaired, even in the very early stages of Parkinson's disease.…”
Section: Referencesmentioning
confidence: 99%